2017
DOI: 10.18632/oncotarget.15267
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB1, c-Rel, and ELK1 inhibit miR-134 expression leading to TAB1 upregulation in paclitaxel-resistant human ovarian cancer

Abstract: The mechanism by which the transcription factors inhibit the miRNA expression in ovarian cancer chemoresistance is unclear. The present study investigated the mechanism underlying the transcriptional repression of miR-134 in chemoresistant serous epithelial ovarian cancer. The results demonstrate that NF-κB1, c-Rel, and ELK1 are involved as transcription factors in repressing miR-134 expression in paclitaxel-resistant ovarian cancer cells. Knockdown of these transcription factors led to increased miR-134 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
(43 reference statements)
2
21
1
Order By: Relevance
“…Nuclear factor-kappa B1 (NF-κB1) is a member of the Rel gene family and involved in the control of tumor cell growth, immune response, apoptosis, and transcriptional regulation. 8 Studies have shown the association of NF-κB1 gene with thyroid cancer, oral squamous cell carcinoma, and colorectal cancer. 9 11 However, there is little research on the association of NF-κB1 and gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor-kappa B1 (NF-κB1) is a member of the Rel gene family and involved in the control of tumor cell growth, immune response, apoptosis, and transcriptional regulation. 8 Studies have shown the association of NF-κB1 gene with thyroid cancer, oral squamous cell carcinoma, and colorectal cancer. 9 11 However, there is little research on the association of NF-κB1 and gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory transcription factor NF-κB has been shown to directly activate Lin28B, and NF-κB is reported to be highly expressed and activated by paclitaxel in several tumor cell lines including Hep3B (Iliopoulos et al, 2009; Shuang et al, 2017). Therefore, we performed a series of experiments to analyze the expression, nuclear translocation, and DNA-binding capacity of NF-κB in Hep3B/TAX cells.…”
Section: Resultsmentioning
confidence: 99%
“…miR-9 is frequently down-regulated in OC and its overexpression in OC cells can down-regulate NF-κB, resulting in reduced proliferation. The NF-κB-miRNA interactions are further supported by a study in serous OC cells, which observed shorter survival of OC patients with high expression of NF-κB [165]. NF-κB repressed miR-134 expression, resulting in increased expression of its target TAB1, and chemoresistance.…”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 86%